Evaluating the efficacy and safety of bladder-sparing regimen with Disitamab Vedotin combined with Toripalimab and pelvic lymph node dissection in muscle-invasive bladder cancer patients: study protocol of a multicenter single-arm phase II trial - Lan, Tianhang; Zhu, Yingying; Zhong, Wenlong; Tan, Qihong; Lin, Tianxin; Huang, Jian; He, Wang (BMC cancer, 2025)
Muscle invasive bladder cancer (MIBC) is a malignancy with high recurrence and metastasis rate. Radical cystectomy and lymph node dissection are the current standard cares for MIBC. The demand for bladder preservation in MIBC patients is growing daily; however, the recognized trimodal bladder-sparing regimen has been shown to have substantial radiation damage and inconsistent efficacy in numerous investigations. In order to address these issues, a secure and efficient bladder preservation program is desperately needed. Therefore, a novel bladder-sparing modality that employing antibody-drug conjugates and immune checkpoint inhibitors combined with pelvic lymph node dissection is worth investigating further in this setting. In this multicenter, single-arm clinical trial, subjects who were diagnosed with muscle-invasive bladder cancer with human epidermal growth factor receptor-2 expression ≥ 2 + will be enrolled. Eligible subjects will receive 12 cycles Disitamab Vedotin combined with Toripalimab treatment and pelvic lymph node dissection after completed transurethral bladder tumor resection, efficacy evaluation would be performed in all of them, patients who achieved clinical complete response will receive 1-year bladder-sparing therapy with Toripalimab immune maintenance treatment. The primary endpoint is 2-year Bladder-intact disease-free survival, and the secondary endpoints include clinical complete response rate, over survival, quality of life, safety and exploratory objectives that biomarkers will be evaluated. Disitamab Vedotin combined with Toripalimab therapy and pelvic lymph node dissection is a promising bladder-sparing treatment option that has the potential to improve the rate of bladder-intact disease-free survival and may become a novel modality of bladder-sparing regimen if the study endpoints are met. This study was registered at Chinese Clinical Trial Registry (ldentifer: ChiCTR2400081555) on March 5, 2024.